2020
DOI: 10.1080/19491034.2020.1815395
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of nuclear F-actin formation and its relevance to cellular phenotypes in Hutchinson-Gilford progeria syndrome

Abstract: Hutchinson-Gilford progeria syndrome (HGPS) is a premature aging disorder caused by a mutation of lamin A, which contributes to nuclear architecture and the spatial organization of chromatin in the nucleus. The expression of a lamin A mutant, named progerin, leads to functional and structural disruption of nuclear organization. Since progerin lacks a part of the actin-binding site of lamin A, we hypothesized that nuclear actin dynamics and function are altered in HGPS cells. Nuclear F-actin is required for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…The importance of actin in the activity of Pol I and Pol II has also been documented [ 37 , 39 ]. Therefore, the presented PIPsLiP-qMS identification of the PIP2-effectors associated with actin cytoskeleton is in agreement with the previous studies that showed involvement of nucleoskeleton in the regulation of gene expression [ 37 , 38 , 39 , 40 , 41 ]. Moreover, the novel PIP2-binding actin- and cytoskeleton-related proteins identified here are interesting candidates for further studies.…”
Section: Discussionsupporting
confidence: 91%
“…The importance of actin in the activity of Pol I and Pol II has also been documented [ 37 , 39 ]. Therefore, the presented PIPsLiP-qMS identification of the PIP2-effectors associated with actin cytoskeleton is in agreement with the previous studies that showed involvement of nucleoskeleton in the regulation of gene expression [ 37 , 38 , 39 , 40 , 41 ]. Moreover, the novel PIP2-binding actin- and cytoskeleton-related proteins identified here are interesting candidates for further studies.…”
Section: Discussionsupporting
confidence: 91%
“…Mahmood et al analyzed several aspects of chromatin state and showed that knocking down β-actin levels altered chromatin structure via chromatin remodelers such as BAF/ BRG1 and EZH2, the latter which we have also shown to be influenced by changes in actin structure 8 , 40 . As well, expression of progerin, the mutant lamin A involved in Hutchinson-Gilford progeria syndrome, also leads to decreased nuclear actin and gene expression, and can be partially corrected by overexpression of nuclear-targeted actin 46 . Insofar as the state of actin, as we confirm in this work, increased nuclear actin promotes transition from the proliferative state and eventually constrains the non-proliferating cell into differentiative phenotypes; increasing the proportion of the branched F-actin form in the nucleus leads to osteoblast lineage while decreased nuclear F-actin leads to adipogenesis 47 .…”
Section: Discussionmentioning
confidence: 99%
“…LMNA-dependent phosphorylation of ERK1/2 causes the phosphorylation of FHOD1/3, inhibiting actin bundling at the nuclear envelope [110]. The regulatory role of lamin A/C in connecting to F-actin fibers results in the loss of nuclear positioning [110], nuclear movement [110], and negates jasplakinolideinduced nuclear F-actin formation in fibroblasts leading to reduced transcription [111]. These observations of lamin A/C loss and nuclear morphology alterations are constant throughout mechanical force stimulation.…”
Section: Nuclear Laminsmentioning
confidence: 94%